The implementation of ‘vocabulary quiz-quiz trade cards’ in the teaching and learning vocabulary among intermediate level primary school students / Rafidah Abd Karim …[et al.] - Abd Karim, Rafidah; Nasri, Nur Farhana; Abdul Rahman, Zarinatun Ilyani; Ahmad Zaidi, Nurul Nadwa; Abdul Rahman, Rosli (Universiti Teknologi MARA Shah Alam, 2018)
In this 21st century, the teaching and learning concept is focusing more on student-centered learning and teacher acts as a facilitator during the process. Most of the issues highlighted are circling around the school students' problems in conversing English and they are unable to work well in group activities as well. Hereby, our team uses the implementation of cooperative learning model Fan-n-Pick for this innovated product. This product aims to enhance primary school students' vocabulary skills and encourage them to work well in group. This product features colourful stacks of cards to be played among four to five players in a group. Therefore, this innovated product is expected to have a good commercial value for primary school students, educators or other sectors.